Program Edukasi Cuci Tangan Pakai Sabun Sebelum Konsumsi Makanan Bergizi Gratis (MBG) di Sekolah Dasar Negeri Inpres Kotaraja, Kota Jayapura - Syaharuddin Nur; Anneke Yacob; Faridha Almira; Fika Daulian; Ilmidin Ilmidin; Petrus Yohanes Ismail Arwimbar; Ulfa Rahmadani; Vrensca Rupilu; Wilma Florensia (I-Com: Indonesian Community Journal, 2025)
The Free Nutritious Meal Program (MBG) in elementary schools aims to improve children’s nutritional status, but its success largely depends on clean and healthy living behaviors (PHBS), especially the habit of handwashing before eating. This community service activity aimed to educate first-grade students at SD Negeri Inpres Kotaraja, Kota Jayapura, about the importance of washing hands with soap before consuming MBG meals. The methods used included simple counseling, demonstration of the six-step handwashing technique, and supporting media such as songs, posters, and educational games. Direct observations were conducted to assess student engagement and behavior changes before mealtime. The results showed that students were enthusiastic in participating and began to develop the habit of handwashing before eating. This program received support from teachers and parents and was considered effective in fostering healthy behavior habits from an early age. This education is expected to support the sustainable success of MBG implementation and increase awareness of PHBS in the school environment.Keywords: Clean and Healthy Living Behavior (PHBS) Education, Handwashing with Soap (HWWS), Free Nutritious Meal Program (MBG), Elementary School, Child Health Empowerment